LPS Stimulation of Cord Blood Reveals a Newborn-Specific Neutrophil Transcriptomic Response and Cytokine Production. Issue 5 (May 2017) - Mathias, Brittany; Mira, Juan C.; Rehfuss, Jonathan P.; Rincon, Jaimar C.; Ungaro, Ricardo; Nacionales, Dina C.; Lopez, M. Cecilia; Baker, Henry V.; Moldawer, Lyle L.; Larson, Shawn D.
ABSTRACT: Background: The neonatal innate immune system differs to microbial infection both quantitatively and qualitatively when compared with adults. Here, we provide the first genome-wide ex-vivo expression profile of umbilical cord blood (UCB) neutrophils from full-term infants prior to and in response to whole-blood lipopolysaccharide (LPS) stimulation. Additionally, we provide cytokine expression prior to and following LPS stimulation. The genomic expression and cytokine profile are compared with LPS-stimulated whole blood from healthy adult subjects (HC). Methods: Whole blood from UCB (n = 6) and HC (n = 6) was studied at baseline or was stimulated for 24 h with 100 ngs/mL of LPS. CD66b + neutrophils were subsequently isolated with microfluidic techniques and genome-wide expression analyses were performed. Ingenuity Pathway Analysis (IPA) software was utilized to predict downstream functional effects. Additionally, cytokine concentrations in whole blood prior to and after 24 h of LPS incubation were determined. Results: LPS stimulated whole blood from UCB demonstrated significant differences in both ex-vivo cytokine production and PMN gene expression. Mixed-effect modeling identified 1, 153 genes whose expression changed significantly in UCB and HC after exposure to LPS ( P  < 0.001 with a minimum 1.5-fold change). IPA downstream predictions suggest that PMNs from UCB fail to effectively upregulate genes associated with activation, phagocytosis, and chemotaxis in response to LPS stimulation. Furthermore, whole blood from UCB showed increased interleukin (IL)-10 production to LPS, but failed to significantly increase several pro-inflammatory cytokines. Conclusions: LPS-stimulated whole blood from UCB exhibited a markedly suppressed inflammatory cytokine production and PMN innate immune genome response. These differences in gene expression and cytokine production may be an adaptive response to a prior fetal environment, but may also explain their increased susceptibility to infections. Characterization of these deficits is the first step toward developing prophylactic and therapeutic interventions.